Среди запахов и звуков: научно-популярная литература / М. С. Плужников, С. В. Рязанцев - Плужников Мариус Стефанович (Эврика, 1991)
Экземпляры: (20150813) / Инвентарный номер: 23560 / Цена: / Сис.шифр: 56.8 / Авт.знак: П 40 / ББК: 56.8